A multifaceted intervention to reduce inappropriate polypharmacy in primary care: research co‐creation opportunities in a pilot study. (18th April 2016) - Anderson, Kristen; Foster, Michele M; Freeman, Christopher R; Scott, Ian A
Summary: Co‐creation (or co‐design) represents the highest form of stakeholder engagement, but it can be infeasible to co‐create with all stakeholders through all stages of a research project. The choice of stakeholders for co‐design will depend on the study purpose and context of change. For this deprescribing pilot study, general practitioners were recognised as a critical gateway for co‐creation, with patients' perspectives of the deprescribing process to be assessed in the evaluation of the pilot.